EFEKTIVITAS IMPLEMENTASI ALOKASI DANA DESA DALAM PEMBANGUNAN SARANA DAN PRASARANA DESA DI KECAMATAN LASOLO KABUPATEN KONAWE UTARA - Muhamad Irfan Rama; Nartin Nartin (Yayasan Akrab Pekanbaru, 2019)
This study reveals the policy of village funds in Belalo Village and Lalowaru Village as a research locus. Village funds as a policy that has been decided by the central government in the framework of accelerating village development must be able to be implemented appropriately and effectively by village government officials as not implementing. Village funds as a government policy can achieve the goals or objectives and positive motivation of the village government as an implementer which is supported through activities or programs that are needed by the community. The facts revealed were contrary to the non-implementation of village funds in Belalo Village and Lalowaru Village such as the questionable facts that were not implemented in implementing village fund policies were the village financial technical implementers consisting of village heads, village secretaries, section heads and village treasurers. There is no village fund implementer to manage village funds with a pattern of self-management.